PROFIL USAHATANI PADI SAWAH DI DESA TOGID KECAMATAN TUTUYAN KABUPATEN BOLAANG MONGONDOW TIMUR (Profile of Rice Farming in Togid Village, Tutuyan District East Bolaang Mongondow Regency) - Christoffel Dumgair; Ribka M. Kumaat; Tommy F. Lolowang (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to describe the profile of lowland rice farming, to analyze farm income, and to determine the feasibility of lowland rice farming in Togid Village, Tutuyan District, Bolaang Mongondow Timur Regency. This research was conducted for three months, from September to November 2021. Respondents were selected using the Simple Random Sampling method. The data were collected by interview using questionnaires. Analysis of the data used in this study were analysis of lowland rice farming income in one growing season and analysis of Return Cost Ratio (R/C).